(untitled) (Development Service Industry Management, 2025)
The rapid digitalization of the global economy has fundamentally transformed the operational landscape of e-business, intensifying competition and necessitating more sophisticated approaches to tactical management. In contemporary electronic markets, tactical decisions – those concerning short-term resource allocation, operational adjustments, and rapid response mechanisms – play a pivotal role in ensuring organizational adaptability, efficiency, and sustained performance. As consumer expectations rise and technological innovations proliferate, the tactical management effectiveness becomes a critical determinant of an enterprise’s competitive positioning. Modern e-business entities operate within highly dynamic environments characterized by accelerated information flows, fluctuating demand patterns, and increased vulnerability to technological and regulatory disruptions. Under such conditions, traditional managerial approaches often demonstrate limited responsiveness and insufficient flexibility. Consequently, the integration of advanced digital tools, data-driven decision-support systems, and adaptive organizational methodologies has emerged as an essential prerequisite for tactical excellence. Enhancing tactical management effectiveness requires a multidimensional approach encompassing digital transformation, analytical capabilities, agile operational structures, customer-centered practices, optimized logistics networks, innovative marketing tactics, and comprehensive risk mitigation frameworks. This study explores key avenues for strengthening tactical management in e-business, highlighting mechanisms through which enterprises can achieve higher levels of operational precision, resilience, and customer value creation. By synthesizing contemporary theoretical insights and practical cases, the analysis underscores how technology adoption, data analytics, agile methodologies, customer-centric tactics, supply chain optimization, strategic marketing, and proactive risk management collectively contribute to elevating tactical performance. Such an integrated perspective provides a foundation for developing robust managerial strategies that align with the complex and fast-evolving realities of digital commerce.